PENGEMBANGAN E-MODUL MATA PELAJARAN MATEMATIKA UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA KELAS VIII DI SMP NEGERI 9 PAGAR ALAM (Studi Pengembangan Pada Mata Pelajaran Matematika Siswa Kelas VIII Di SMP Negeri 9 Pagar Alam) - Firmansyah Firmansyah (DIADIK, 2021)
The aim of this study was to produce learning media in the form of interactive e-modules to improve students' learning achievement in mathematics class VIII at SMP Negeri 9 Kota Pagar Alam. In this study, a development design (Development Research) was used. The research subjects were Grade VIII students of SMP Negeri 9 Pagar Alam. The data collection techniques used in the study were assessment sheets and student test results. The data analysis used mean and t-test. The material and media expert validation instrument in the study was a Likert scale. The conclusion of this research is that the mathematics E-module developed interactively, is of high quality and feasible as a learning medium at SMP Negeri 9 Kota Pagar Alam class VIII in terms of media components, material, and learning process as well as in terms of appearance, text, images, videos, and operation. The development of e-mathematics modules is effective in improving student learning achievement based on the results of limited-scale and wide-scale trials, there are significant differences